O brincar: a produção acadêmica do GT da ANPED - Silva, Náira Shelda Aquino (Brasil, 2022)
This research aimed to map and analyze the productions on playing in the annals of GT 07 of ANPEd in the last ten years (2011-2021). To conduct this investigation, we worked with a qualitative approach and with the methodology of bibliographic research and descriptive analysis. We used as methodological procedures the search in the GT annals from the descriptor “brincar” and later the reading of the abstracts. Eight (8) works were mapped. We found in the investigations the importance of playing for early childhood from the perspective of different fields of studies, pedagogy, anthropology, psychology and sociology of childhood, using as theoretical reference Tizuko Kishimoto, Lev Vygotsky, Gilles Brougére, and Wiliam Corsaro, scholars and theorists already consolidated in the area of childhood and play studies. . It also highlights in the analysis of these productions the breadth of research on the theme of play, as each author emphasizes in an analysis perspective that firstly contemplates the playful as a primordial axis for the teaching and learning process, however the titles of the research are very different from each other.